Questionnaire survey on the satisfaction of SimEx dental education system - Guang Hong; Chun-Cheng Hung; Gen Mayanagi; Takashi Nishioka; Lu Sun; Eddie Hsiang-Hua Lai; Ting-Hsun Lan; Keiichi Sasaki; Nobuhiro Takahashi (Elsevier, 2023)
Background/purpose: The SimEx is dental training system that applies new technology in a computerized dental simulator. The purpose of this study was to understand the usability satisfaction of the SimEx dental education and evaluation system by dental students and dentists at Tohoku University. Materials and methods: In this study, the Tohoku University IRB execution number was 2020-3-33. The number of subjects accepted was 59 at Tohoku University and divided into 4 groups based on years of clinical experience (Group A: 0 years; Group B: 1-2 years; Group C: 2-5 years; Group D: at least 5 years), and a total of 58 usability questionnaires were collected. Subjects completed the SimEx Usability Satisfaction Questionnaire after operating the SimEx (EPED Inc., Kaohsiung, Taiwan) course, which contained 16 questions. Results: Among the 58 questionnaires collected by Tohoku University, there were 19 undergraduate students (4th∼6th grade), 12 post-graduate students, 14 residents, and 13 dentists. Significant differences between Group A and Group B, and between Group A and Group D were found (P < 0.05). The same results were obtained for the "experience satisfaction index". In the items where significant differences were found, longer clinical experience tended to result in lower scores. Conclusion: From these results, we can conclude that the SimEx education and evaluation system facilitates students' self-learning, and this system is very useful for continued study and clinical skill training for dentists, especially for students and junior dentists with high usability satisfaction.